2016
DOI: 10.1111/cjag.12129
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Urban Landscaping: Consumer Preferences and Willingness to Pay for Turfgrass Fertilizers

Abstract: Residential lawns provide diverse benefits, including social (e.g., enhancing humans' physical and psychological well-being), economic (e.g., increasing real estate values), and environmental (e.g., supporting local ecosystems) benefits. However, improper lawn fertilizer applications can cause adverse environmental consequences, such as excessive chemical runoff into adjoining watersheds leading to water contamination. Currently, the importance of eco-friendly fertilizers to homeowners has not been assessed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 77 publications
(133 reference statements)
1
9
0
Order By: Relevance
“…Hilaire et al (2008) and Yanko (1992), subjects in this study may have preferred fresh water because of concerns about or lack of information regarding the safety of recycled water (gray water). Clearly, this is a point for future education, especially for nurseries striving to conserve water resources in other work has shown that sustainability concerns from consumers often translate into substantial willingness to pay price premiums (Behe et al, 2010(Behe et al, , 2013Getter and Behe, 2013;Khachatryan et al, 2016). The use of biodegradable containers, e.g., translates into higher price premiums for ornamental products .…”
Section: Discussionmentioning
confidence: 99%
“…Hilaire et al (2008) and Yanko (1992), subjects in this study may have preferred fresh water because of concerns about or lack of information regarding the safety of recycled water (gray water). Clearly, this is a point for future education, especially for nurseries striving to conserve water resources in other work has shown that sustainability concerns from consumers often translate into substantial willingness to pay price premiums (Behe et al, 2010(Behe et al, , 2013Getter and Behe, 2013;Khachatryan et al, 2016). The use of biodegradable containers, e.g., translates into higher price premiums for ornamental products .…”
Section: Discussionmentioning
confidence: 99%
“…Both studies suggest using production practices as a means of differentiating ornamental plants but that plant type influences the effect on consumer choices. Similarly, and Khachatryan et al (2016) recently reported that consumers' were willing to pay price premiums for organically grown ornamental plants and organic fertilizers. One would expect production practices that are associated with human health (e.g., organic production reducing consumers' pesticide exposure) to be more important for products that are potentially consumed (Yue et al, 2011).…”
mentioning
confidence: 98%
“…Seed nit is the presence of seeds, and Price it is the price variable with a nonrandom parameter. The coefficient for the price coefficient is assumed to be fixed to guarantee the normal distribution of willingness to pay estimates (Gao and Schroeder, 2009a,b;Khachatryan et al, 2017;Train, 2009). Morevoer, WTP values were calculated as a negative ratio of the non-price attribute coefficient to price coefficient, such as:…”
Section: Econometric Model ■ Random Parameter Logit Modelmentioning
confidence: 99%